Desain dan Analisis Barrier Gate Otomatis Berbahan Komposit Serat Glass dan Serat Daun Gewang (Hibrid Polyester) pada Bagian Palang - Afrianus Serfano; Erich U.K. Maliwemu; Ishak S. Limbong (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2021)
Barrier Gate is a stopping mechanism that has a function for the security of a place such as the entrance to an office or agency. The design and analysis of the construction of the automatic barrier gate made of glass fiber composite and leaf gewang fiber (hybrid polyester) aims to limit crowds so that safety and comfort are always maintained. This test uses software solidwork 2015. The results of the analysis of three variations of the crossbar components are, variation 1 with a maximum stress of 12.255 Mpa, variation 2 with a maximum stress of 10.217 Mpa and variation 3 with a maximum stress of 37.359 Mpa. Of the 3 variants, the one that produces the better stress is variant 3 with a length of 250 cm width 3 cm and a thickness of 4 cm which gets the largest with a value of 37.359 MPa. Static analysis of frame components with a length of 40 cm width 40 cm and a height of 100 cm, resulted in a maximum stress of 7.499 MPa and a maximum displacement of 0.134 mm.